Enlil, Isaiah, and the Origins of the‌ʾ‌ĕlîlîm: A Reassessment - Hays, Christopher B. (Zeitschrift für die alttestamentliche Wissenschaft, 2020)
The characteristically Isaianic term אליל for other gods does not have its roots in an earlier Semitic adjective, as has often been thought. Rather, it was adopted from Akkadian Illil/Enlil into Hebrew because it reflected the rhetoric of Neo-Assyrian rulers. As in Akkadian, it was used in an extended sense to refer to major divinities; and it was retained in the Isaianic tradition presumably because it was a useful term for »false gods«—readily comprehensible even as a new coinage, yet distinct from the terms used for Yhwh. As anti-idol polemics became increasingly prominent and vicious, the latest Isaianic tradents avoided אליל, preferring more overt terms for idols. Eventually, it came to be reanalyzed as an adjective and used as a mere insult: »worthless«.